Atmospheric nitrate leached from small forested watersheds during rainfall events: Processes and quantitative evaluation. Issue 8 (3rd August 2016) - Osaka, Ken'ichi; Kugo, Tatsuro; Komaki, Naoto; Nakamura, Takashi; Nishida, Kei; Nagafuchi, Osamu
Abstract: To determine the availability of atmospheric NO3 − deposition on forested ecosystems and to understand the interaction between the nitrogen cycle in a forest ecosystem and atmospheric nitrogen input/output, we quantitatively evaluated the atmospheric NO3 − passing through forested watersheds by measuring δ 18 ONO3 leaching during rainfall events in two forest ecosystems (Su‐A and Ab‐S). Atmospheric NO3 − leaching in rainfall events was clearly higher in Ab‐S than in Su‐A, even for a similar amount of rainfall, which demonstrated that atmospheric NO3 − leaching differs among forested watersheds. Our observations suggest that a large part of the atmospheric NO3 − leached from the watersheds was derived from surface soil, which was deposited before rainfall events occurred; however, direct atmospheric NO3 − leaching via throughfall discharge also contributed, especially at the beginning of rainfall events. In Ab‐S, 2.9–37.8% (average = 15.5%) of atmospheric NO3 − deposition passed through the watershed, accounting for 3.1–49.8% (average, 26.4%) of the total NO3 − leached during rainfall events. The NO3 − input was not large, and the NO3 − pool and net nitrification rate were small; therefore, nitrogen was not saturated in the soil at Ab‐S. Nevertheless, some of the atmospheric NO3 − deposition was not assimilated and was leached immediately. Moreover, our observations suggest that the hydrological characteristics of the watersheds, which control the ease of rainwater discharge, strongly influenced the rate of atmospheric NO3 − leaching. This suggests that the hydrological characteristics of watersheds influence the availability of atmospheric NO3 − deposition in forested ecosystems and the progression of nitrogen saturation. Key Points: Atmospheric NO3 − leaching rates differed among forested watersheds 2.9–37.8% of atmospheric NO3 − deposition passed through the watershed in our study The hydrological characteristics of watersheds strongly influence atmospheric NO3 − leaching